2021
DOI: 10.2147/jmdh.s298196
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Caregivers’ Burden and Neuropsychiatric Symptoms in Female Patients with Alzheimer’s Disease with Varying Dementia Severity

Abstract: Purpose This study examined the attributes causing higher burdens for caregivers caring for female patients with Alzheimer’s disease by analyzing a combination of various variables, including demographic data, dementia severity, and neuropsychiatric symptoms. Patients and Methods This study included 99 female patients with Alzheimer’s disease who were cared for by the dementia collaborative care team at Changhua Christian Hospital, Taiwan. Neuropsychiatric symptoms used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 27 , 28 The Apriori algorithm, which has been applied in dementia-related studies, was employed in this study to find statistical associations between any of the attributes by satisfying both minimum support and confidence threshold values along with lift >1. 6 , 7 , 29–33 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… 27 , 28 The Apriori algorithm, which has been applied in dementia-related studies, was employed in this study to find statistical associations between any of the attributes by satisfying both minimum support and confidence threshold values along with lift >1. 6 , 7 , 29–33 …”
Section: Methodsmentioning
confidence: 99%
“… 4–6 Family caregivers played an important role in caring for patients with Alzheimer’s disease (AD), but the caregiving load often brought the problems in their mental and physical health. 7 For dementia caregivers, the prevalence of caregivers’ depression ranged from 30%-83%. 8–11 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the demographic, health, socioeconomic status 6 , and mental well-being 7 are related to caregivers' burden. Additionally, domestic literature found that the severity of mental and behavioral symptoms in a case predicted a higher care load 8,9 , especially when a person with dementia started to experience delusional hallucinations 10 .…”
Section: Introductionmentioning
confidence: 99%